Data For Publication "Committed Sea-Level Rise Under The Paris Agreement And The Legacy Of Delayed Mitigation Action". - Mengel, Matthias (Zenodo, 2017)
Data underlying the publication "Committed sea-level rise under the Paris Agreement and the legacy of delayed mitigation action". Journal: Nature Communications Authors: Matthias Mengel 1* , Alexander Nauels 2 , Joeri Rogelj 3,4 , Carl-Friedrich Schleussner 1,5 (1) Potsdam Institute for Climate Impact Research (PIK), Member of the Leibniz Association, P.O. Box 60 12 03, D-14412 Potsdam, Germany (2) Australian-German College of Climate & Energy Transitions, The University of Melbourne, Parkville, Victoria 3010, Australia (3) ENE Program, International Institute for Applied Systems Analysis (IIASA), Schlossplatz 1, Laxenburg A-2361, Austria (4) Institute for Atmospheric and Climate Science, ETH Zurich, Universitätstrasse 16, Zurich 8006, Switzerland (5) Climate Analytics, Ritterstr. 3, 10969 Berlin, Germany (*) email matthias.mengel@pik-potsdam.de Abstract: Sea-level rise is a major consequence of climate change that will continue long after emissions of greenhouse gases have stopped. The 2015 Paris Agreement aims at reducing climate-related risks by reducing greenhouse gas emissions to net zero and limiting global-mean temperature increase. Here we quantify the effect of these constraints on global sea-level rise until 2300 including Antarctic ice-sheet instabilities. We estimate median sea-level rise between 0.7 and 1.2m if net zero greenhouse gas emissions are sustained until 2300, varying with the pathway of emissions during this century. Temperature stabilization below 2°C is insufficient to hold median sea-level rise until 2300 below 1.5m. We find that each 5-year delay in near-term peaking of CO2 emissions increases median year-2300 sea-level rise estimates by ca. 0.2m, and extreme sea-level rise estimates at the 95th percentile by up to 1m. Our results underline the importance of near-term mitigation action for limiting long-term sea-level rise risks. Large zip files provides data. Small zip file python code for plotting and writing supplementary data.